Daddy's girls - Steel, Danielle (New York : Delacorte Press, 2020)
Decades ago, after the death of his wife, Texas ranch hand JT Tucker took his three small daughters to California to start a new life. With almost no money, a will of iron, and hard work, he eventually built the biggest ranch in California. But when he dies suddenly at the age of sixty-four, the ranch is inherited by his three daughters$1 (Beach of them finding it impossible to believe that this larger-than-life figure is gone from their lives.s
A novel.
Keywords: Sisters -- Fiction; Fathers and daughters -- Fiction; Grief -- Fiction; Family secrets -- Fiction; Ranches -- California -- Fiction; California -- Fiction; Domestic fiction